Association of Ratio of Apolipoprotein B to Apolipoprotein A1 With Survival in Peritoneal Dialysis - Yu, Jing; Xia, Xi; Huang, Na-Ya; Qiu, Ya-Gui; Yang, Xiao; Mao, Hai-Ping; Chen, Wei; Huang, Feng-Xian (Frontiers in Nutrition, 2022)
Background Although the ratio of apolipoprotein B (apo B) to apolipoprotein A1 (apo A1) (apo B/apo A1) seems to be associated with mortality in hemodialysis (HD) patients, the association of apo B/apo A1 ratio with death remains not clear in peritoneal dialysis (PD) patients. Aims The study targets to examine the relationship of apo B/apo A1 ratio with survival in patients receiving PD treatment. Methods In this single-center prospective observational cohort study, we enrolled 1,616 patients receiving PD treatment with a median follow-up time of 47.6 months. We used a multivariable Cox proportional hazards model to examine the relationship between apo B/apo A1 ratio and cardiovascular (CV) and all-cause mortality. The association of apo B/apo A1 ratio with atherosclerotic and non-atherosclerotic CV mortality was further evaluated by competing risk regression models. Results During the follow-up, 508 (31.4%) patients died, 249 (49.0%) died from CV events, of which 149 (59.8%) were atherosclerotic CV mortality. In multivariable models, for 1-SD increase in apo B/apo A1 ratio level, the adjusted hazard ratios for CV and all-cause mortality were 1.26 [95% confidence interval (CI), 1.07–1.47; P = 0.005] and 1.20 (95% CI, 1.07–1.35; P = 0.003), respectively. The adjusted subdistribution hazard ratios for atherosclerotic and non-atherosclerotic CV mortality were 1.43 (95% CI, 1.19–1.73; P < 0.001) and 0.85 (95% CI, 0.64–1.13; P = 0.256), respectively. For quartile analysis, patients in quartile 4 had higher CV, all-cause, and atherosclerotic CV mortality compared with those in quartile 1. Moreover, apo B/apo A1 ratio had a diabetes-related difference in CV, all-cause, and atherosclerotic CV mortality. Conclusion Elevated apo B/apo A1 ratio level was significantly associated with CV, all-cause, and atherosclerotic CV mortality in patients undergoing PD. Moreover, the association was especially statistically significant in patients with diabetes.